Pengaruh Sosial Media Marketing Melalui Instagram Terhadap Minat Beli Konsumen Tenun Ana Sukarara - Wardi, Putri; Nirwana, Baiq Nadia (CV Insan Kreasi Media, 2023)
The current development of technology and information has made business in the world increasingly rapid so that business opportunities, both goods and services, are opened. Therefore, business people are required to be more careful in business competition in order to remain in the competition. Businessmen must pay attention to marketing to consumers so that consumers are interested in buying the products offered. This condition causes business people to try to find the right strategy in marketing their products. One of the strategies undertaken by business people is social media marketing through Instagram which is positive in the minds of consumers. This study uses the purchase interest theory from Ferdinand's source (2002: 129) and Lidyawatie (2008:78). The purpose of this study was to determine how far Social Media Marketing affects Ana Sukarara's consumer buying interest. The method used in this study is a survey sample method with data obtained through a Google Form questionnaire to 100 respondents. The results showed that Social Media Marketing has an influence with a significance level of 0.000, this indicates that Social Media Marketing has a significant positive effect on purchase intention.